Effect of Hemifacial Spasm on Intraocular Pressure Measurement - Erdogan Cicik; Rengin Yildirim; Ceyhun Arici; Funda Dikkaya; Osman Sevki Arslan (Journal of Ophthalmology)
Purpose. To evaluate the effect of hemifacial spasm (HFS) on intraocular pressure (IOP) measurement. Methods. Twenty-four consecutive patients with HFS and 25 age- and gender-matched randomly selected eyes of healthy volunteers underwent corneal pachymetry and IOP measurements using Goldmann applanation tonometer (GAT) and noncontact tonometer (NCT). IOP measurements were performed before (during HFS) and 2 weeks after Botox injections in HFS patients and in healthy volunteers without Botox injections. Results. There was no statistical difference between involved eye side and uninvolved eye side of HFS patients in measured central corneal thickness. Similarly, no difference was found between involved eye side of HFS patients and controls. There were no statistically significant differences comparing IOP values before treatment and levels measured at 2 weeks of Botox injections, either with GAT (p=0.33, 0.11) or NCT (p=0.80, 0.43) devices in the involved eyes and uninvolved eyes of patients with HFS, respectively. There were also no significant differences in these parameters (GAT (p=0.63) and NCT (p=0.54)) in controls. Conclusions. Contractions in facial muscles may not lead to significant increase in IOP in HFS patients. This result may help clinical decision making in the treatment of glaucoma patients with HFS. This trial is registered with NCT03390803.